Spatiotemporal dynamics and influencing factors of native and invasive saltmarshes in a rapidly silting bay during 1985–2023 - Mingshan Xu; Mingshan Xu; Mingshan Xu; Jiali Gu; Peng Yun; Jianjun Gan; Wenzhou Fan; Zhentao Chen; Jie Shao; Guangzhi Zhang; Jian Zeng (Frontiers in Marine Science)
Globally, native saltmarshes are declining, while invasive saltmarshes are expanding rapidly. However, the underlying processes and driving mechanisms behind these trends remain poorly understood, particularly in rapidly silting coastal bays. Here, we investigated the spatiotemporal dynamics and influencing factors of native saltmarshes (Scirpus mariqueter and Phragmites australis) and invasive Spartina alterniflora in Yueqing Bay, eastern China, by interpreting Landsat series images during 1985-2023. Results showed that native saltmarshes significantly decreased from 632.24 ha to complete disappearance, while S. alterniflora expanded from zero to 2872.90 ha in Yueqing Bay during 1985-2023. Specifically, S. mariqueter experienced a notable decline from 1985 to 1995, subsequent growth between 2000 and 2005, and another reduction from 2005 to 2010. P. australis expanded from 2005 to 2010 but shrank from 2010 to 2015 as S. alterniflora encroached upon its habitats. By contrast, S. alterniflora consistently expanded annually, except when it was eradicated by human interference. Both natural factors and human activities influenced native and invasive saltmarshes; for instance, mudflat reclamation facilitated saltmarsh expansion by creating suitable habitats during a certain period, particularly for S. alterniflora. From 1984 to 2018, the coastline extended seaward, causing sedimentation and landward transformation, which contributed to the expansion of S. alterniflora. However, the 118.05 ha mangrove forests negatively impacted S. alterniflora, as planting mangroves often involves the removal of existing S. alterniflora. Additionally, maximum tidal range and mean annual temperature positively affected saltmarshes. Our study highlighted the influence of natural factors and human activities on the spatiotemporal dynamics of both native and invasive saltmarshes in rapidly silting bays, underscoring the urgent need for conservation, restoration, and management of native saltmarshes.